1996
DOI: 10.1007/s002530050736
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of a novel microbial lactate oxidase

Abstract: Geotrichum candidum was found to produce a lactate oxidase. The enzyme was purified by gel filtration and ion-exchange chromatography. The purified lactate oxidase showed a molecular mass of 50 kDa under denaturing and about 400 kDa under non-denaturing conditions. Transmission electron microscopy analysis confirmed an octameric structure. FMN was found to be a cofactor for this enzyme. Polarographic studies confirmed an oxygen uptake by the lactate oxidase. The enzyme showed specificity towards the L isomer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The estimated apparent K m and V max of GOX2071 toward D-lactate were 3.62 Ϯ 0.53 mM and 0.52 Ϯ 0.05 U/mg, respectively ( Table 7). The data are similar to those reported for L-lactate oxidase from Geotrichum candidum (K m , 3.6 mM; V max , 1.26 U/mg) (36).The estimated apparent K m and V max for O 2 , the other substrate, were 0.16 Ϯ 0.01 mM and 0.97 Ϯ 0.03 U/mg, respectively (Table 7).…”
Section: Resultssupporting
confidence: 78%
“…The estimated apparent K m and V max of GOX2071 toward D-lactate were 3.62 Ϯ 0.53 mM and 0.52 Ϯ 0.05 U/mg, respectively ( Table 7). The data are similar to those reported for L-lactate oxidase from Geotrichum candidum (K m , 3.6 mM; V max , 1.26 U/mg) (36).The estimated apparent K m and V max for O 2 , the other substrate, were 0.16 Ϯ 0.01 mM and 0.97 Ϯ 0.03 U/mg, respectively (Table 7).…”
Section: Resultssupporting
confidence: 78%
“…G. candidum possesses an array of enzymes with great potential for biotechnological applications. Its lactate oxidase has been used to determine lactate levels implicated in heart disease (95). In toxic waste management, G. candidum is used to decolorize azo dyes in industrial waste water (96), and its peroxidases have shown high efficiency in decolorizing and biodegrading olive mill wastewater, a pollutant generated by olive oil extraction (97).…”
Section: Geotrichum Candidum: the Goodmentioning
confidence: 99%
“…20 Indeed, through its lactate oxidase, G. candidum catalyses the reaction leading from lactate to pyruvate and hydrogen peroxide. 22 Lactic acid was therefore preferred over the remaining peptides and amino acids as an energy source during stationary state. A lower amount of energy was thus required during stationary state, leading to a decrease in the CO 2 production (Fig.…”
Section: Resultsmentioning
confidence: 99%